The war that used up words - Hutchison, Hazel. (New Haven ; London)
x, 292 s.
Keywords: "In this provocative study, Hazel Hutchison takes a fresh look at the roles of American writers in helping to shape national opinion and policy during the First World War. From the war’s opening salvos in Europe, American writers recognized the impact the war would have on their society and sought out new strategies to express their horror, support, or resignation. By focusing on the writings of Henry James, Edith Wharton, Grace Fallow Norton, Mary Borden, Ellen La Motte, E. E. Cummings, and John Dos Passos, Hutchison examines what it means to be a writer in wartime, particularly in the midst of a conflict characterized by censorship and propaganda. Drawing on original letters and manuscripts, some never before seen by researchers, this book explores how the essays, poetry, and novels of these seven literary figures influenced America’s public view of events, from August 1914 through the Paris Peace Conference of 1919, and ultimately set the literary agenda for later, more celebrated texts about the war." --